EFEKTIVITAS HUKUM LINGKUNGAN DALAM MENGHADAPI MASALAH YANG DITIMBULKAN OLEH ROKOK - Fitriah, Siti Kamilah; Ghefyra, Rahma; Amrullah, Ulul Abshor; Alfatih, Zaidi Hamzah (Gapenas Publisher, 2025)
This article explores the effectiveness of environmental laws in addressing the problems caused by smoking. Although public health regulations have been implemented to reduce the amount of cigarette consumption, the environmental impact of smoking is often ignored. This research focuses on existing environmental policies, such as waste management, environmental protection, and pollution control, and the extent to which these policies can overcome environmental problems related to smoking. Using analytical methods and case studies, this article identifies weaknesses in the implementation of existing laws and recommends corrective actions. The results suggest that integration of health and environmental legislation will create better strategies in reducing the negative impact of smoking on the environment.